2009
DOI: 10.1111/j.1462-5822.2008.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

UropathogenicEscherichia coliAL511 requires flagellum to enter renal collecting duct cells

Abstract: SummaryEscherichia coli is the leading cause of urinary tract infections, but the mechanisms governing renal colonization by this bacterium remain poorly understood. We investigated the ability of 13 E. coli strains isolated from the urine of patients with pyelonephritis and cystitis and normal stools to invade collecting duct cells, which constitute the first epithelium encountered by bacteria ascending from the bladder. The AL511 clinical isolate adhered to mouse collecting duct mpkCCD cl4 cells, used as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 41 publications
1
50
0
Order By: Relevance
“…Similarly, the ability of E. coli O83:H1 to adhere to and invade Caco-2BBe or T84 monolayers was shown to be dependent on these structures (8). Flagella have also been involved in the internalization of uropathogenic E. coli into collecting duct cells in vitro (30).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, the ability of E. coli O83:H1 to adhere to and invade Caco-2BBe or T84 monolayers was shown to be dependent on these structures (8). Flagella have also been involved in the internalization of uropathogenic E. coli into collecting duct cells in vitro (30).…”
Section: Discussionmentioning
confidence: 97%
“…A ⌬fliC derivative of 1711-4 was constructed by the one-step allelic exchange recombination method as described earlier (5,6,30). Primers containing a 40-bp region homologous to the 5Ј (fliCH40.zeo-5) and 3Ј (fliCH40.zeo-3) extremities of the fliC gene and specific sequences for the Zeo resistance-encoding gene were used to amplify the Zeo cassette ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…For standard ultrastructure analyses, dissected tail segments from anesthetized embryos were fixed overnight at 4°C in 2.5% glutaraldehyde in 0.1 M Na cacodylate buffer, postfixed for 1 h in the same buffer containing 1% osmium tetroxide, dehydrated through a graded series of ethanol, and then embedded in an Epon-Araldite resin (33). Thin sections (50 to 70 nm) were cut using a Leica Ultracut-ECT microtome, stained for 4 min with 4% uranyl acetate, and observed under a Jeol (Croissy sur Seine, France) Jem 1010 transmission electron microscope at 80 kV.…”
Section: Methodsmentioning
confidence: 99%
“…Competitive in vivo experiments in mice have demonstrated that flagella contribute to the fitness of UPEC during colonization of the UT (Lane et al, 2005;Wright et al, 2005), and transient expression of flagella enhances bacterial ascent from the bladder to the kidneys (Lane et al, 2007b). In the kidneys, motility as well as the flagellar filament itself are apparently required for bacterial invasion into cells of renal collecting ducts (Pichon et al, 2009), which also are targets for fimbriae-mediated adherence of UPEC (Korhonen et al, 1986). For newborn meningitis-associated E. coli (NMEC), which represents another extraintestinal E. coli pathogroup, the flagellar structure rather than the motility function has been shown to be relevant for bacterial association with and invasion into human brain microvascular endothelial cells (Parthasarathy et al, 2007).…”
Section: Introductionmentioning
confidence: 99%